Extending Coronectomy Indications to Third Molars with Taurodontism to Prevent Paresthesia and Mandible Fracture - Polianne Alves Mendes; Isabela Moreira Neiva; Cláudia Borges Brasileiro; Ana Cristina Rodrigues Antunes Souza; Leandro Napier Souza (Case Reports in Dentistry)
Taurodontism is considered a dental anomaly responsible for a morphoanatomical change in the shape of the tooth in which the roots are reduced in size but the body of the tooth is enlarged and bulky. The aim of this paper is to present a case of a 25-year-old female patient with taurodontism of mandibular partially erupted third molars, presenting a high risk of angle fracture and paresthesia in case of their removal, treated by means of coronectomy. The postoperative period was uneventful and the patient remained in follow-up for 12 months. In conclusion, the identification of third molars with higher risk of complications related to their extractions is the key to consider conservative measures to avoid problems. Coronectomy is a relatively simple technique that should be taken into account when considering bulky, deeply located third molars with a high risk of paresthesia or mandibular fracture, even in presence of taurodontism.